The effect of premolar extractions on the change of angulation and eruption space of the mandibular third molars after orthodontic treatment - Asmae BENKADDOUR; Khaoula M’RABT; Loubna BAHIJE; Fatima ZAOUI; Asmae BAHOUM (International Arab Journal of Dentistry (IAJD), 2025)
Objectives: Our study was designed to analyze the effect of lower premolar extraction on the eruption space, position, and angulation of the lower third molars during orthodontic treatment.Methods: This was a cross-sectional, retrospective, descriptive, and analytical study comparing two groups of patients: the first group included 20 patients treated without premolar extraction, and the second group, 27 patients treated with premolar extraction. Linear and angular measurements were performed on panoramic radiographs and lateral cephalograms taken before and after orthodontic treatment.Results: The eruption space and the horizontal position of the lower third molars showed favorable and statistically significant changes between the two groups. However, changes in angulation did not show a significant difference.Conclusions: Premolar extractions have a positive and significant influence on the eruption space and horizontal position of the mandibular third molars. Although angulation changes were favorable in the extraction group, they were not statistically significant.